PENERAPAN ALGORITMA INTERPOLATIVE CODING PADA APLIKASI KOMPRESI FILE GAMBAR - Agung Dwi Pradana; Imam Saputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The large amount of data that has been stored in memory or hard disk will result in increasing the amount of usage capacity on the storage media. Large file sizes can also affect the time of sending or transferring data between storage media. Therefore humans conduct a study in order to have alternative ways to overcome these problems, one of them is by means of compression techniques. In this research, an image file compression application program was built using the interpolative coding method. In building applications using Visual Basic.Net software. The construction of this application is expected to reduce storage media capacity usage. In this testing phase is done with an image file type that is a test file with RGB color type.Keywords: Compression, Image file, Interpolative Coding Algorithm